2018
DOI: 10.1002/jcu.22660
|View full text |Cite
|
Sign up to set email alerts
|

Multinodular fatty change in the liver in three patients with chronic hepatic porphyria: Contribution of sonography to the diagnosis

Abstract: We present three cases of chronic hepatic porphyria (CHP) in alcoholic patients, in which grayscale ultrasound (US) revealed multiple echogenic masses in the liver, mimicking multinodular hepatocellular carcinoma on alcoholic liver injury. In all cases, contrast-enhanced US (CEUS) showed iso-enhancement of the mass lesions throughout all vascular phases. Additionally, twodimensional shear wave elastography (2DSWE) (performed in two cases) revealed the mass to have almost the same SWE value as the surrounding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Naganuma et al hypothesized that patients with hyperechoic rims had less fatty changes than those with a homogeneous hyperechoic pattern. 25 It was also confirmed that in many cases, there was partial confluence and no mass effect in the vascular structures, which suggests that these nodules occur due to degeneration rather than tumors. Furthermore, the irregular pattern of fat deposition observed in Case 4, called "geographic" fatty liver, indicates that PCT can lead to various forms of fat deposition.…”
Section: Casementioning
confidence: 80%
See 4 more Smart Citations
“…Naganuma et al hypothesized that patients with hyperechoic rims had less fatty changes than those with a homogeneous hyperechoic pattern. 25 It was also confirmed that in many cases, there was partial confluence and no mass effect in the vascular structures, which suggests that these nodules occur due to degeneration rather than tumors. Furthermore, the irregular pattern of fat deposition observed in Case 4, called "geographic" fatty liver, indicates that PCT can lead to various forms of fat deposition.…”
Section: Casementioning
confidence: 80%
“…Multiple hyperechoic nodules due to focal steatosis are important as diagnostic triggers for PCT and for differential disease from cancer. Many reports have shown that focal fatty changes can present as multiple hyperechoic nodules in the liver in patients with PCT 5,6,9–25 . However, the incidence of liver nodules in patients with PCT is unknown, and it is possible that some patients with PCT may not have been diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations